Improving quality of maternal and newborn care: An evaluation of enablers and barriers in implementing emergency obstetric and newborn care training in Bhutan and Lao People's Democratic Republic. - Sabera Turkmani; Kara Blackburn; Catherine Breen-Kamkong; Karma Tshering; Karma Choden; Alanya Chalernphon; Keodompone Vilivong; Rachel Smith; Caroline Homer (PLOS Global Public Health, 2025)
This study evaluates the effectiveness and sustainability of UNFPA-supported Emergency Obstetric and Newborn Care (EmONC) in-service training programs in Bhutan and Lao PDR, aiming to improve maternal and neonatal health services by enhancing health providers' competencies in performing Basic EmONC signal functions. This study employed qualitative interviews with key informants and healthcare providers to identify enablers and barriers to the training program's rollout and explore its sustainability. Overall, the EmONC training in Bhutan and Lao PDR was recognised as positive in enhancing the knowledge, skills, and confidence of healthcare providers and contributing to improved quality of care for women and newborns. Despite the successes, there are noted challenges such as financial and resource limitations, lack of alignment of policy and practice, legal barriers, insufficient mentoring and supportive supervision, and high workloads, which impeded the effectiveness and sustainability of the training. Future initiatives should focus on the long-term impact of EmONC training programs, examining how sustained policy reforms and regulatory alignment can empower healthcare providers to perform life-saving skills, ultimately improving maternal and newborn health outcomes.